Setting a Benchmark for REIT Performance in Malaysia - Olaopin Olanrele, Olusegun; Said, Rosli; Daud, Md Nasir (International Journal of Property Sciences (E-ISSN: 2229-8568), 2015)
The percentage performance of a REIT is not the most important but the reliability of the performance in absolute terms to a relevant index or benchmark is key to assessing REIT index or benchmark. This paper focuses on the construction of a performance benchmark for REIT sector in Malaysia. The study explores the literature on performance and benchmarking, appraises REIT performance analyses as presented in past studies, and proposes REITs return benchmark using Time series forecast. The study adopts a quantitative analysis approach. Ten listed conventional REITs were purposively selected to reflect diversity in portfolio and location. Data was extracted from annual reports of selected REIT companies through their websites for an eight-year transaction period (2006-2013). Time series regression was performed on the collected data from the listed REITs to establish a linear model for the forecast of REIT return at any period that can serve as a benchmark for the REITs. The study found that Malaysian REIT performed 27.5% lower than the forecast for 2013 but outperformed the KLCI index. M-REIT has the capacity to do better than the 6.8% recorded for 2013. The study did not extend to the Islamic REITs in Malaysia.